Functional morphology and identity of the thenar pad in the subterranean genus Ctenomys (Rodentia, Caviomorpha) - Echeverría, Alejandra Isabel (2019)
As in many other fossorial tetrapods, the most obvious adaptations to scratch-digging in the subterranean tuco-tuco (Rodentia, Ctenomyidae, Ctenomys) are found in the hands, which among other adaptations, present the mesaxonic condition; i.e. the central digits are more developed, and also their claws, which are curved and elongated. The thumb is atrophied and aligned with the rest of the digits, showing a small and flat claw. This configuration of digits and claws seems to be in accordance with what it is expected for rodents: rudimentary movements when handling food items. However, on the palmar side of the hand, tuco-tucos have several pads, the thenar (located under the thumb) being the most developed. In this study, we investigated the functional morphology of the thenar pad through different approaches: musculoskeletal anatomy, histology and functionality. The analysis of radiographs and clarified and double-stained hand samples of Ctenomys talarum and C. australis showed that the thenar pad is supported by a paddle-shaped bone that articulates with a protrusion in the scapholunate bone. This bone, flat and long, continues in a flat cartilaginous structure, with a shape similar to a claw. Dissections showed that the thenar pad has several associated muscles: the m. palmaris longus, the m. abductor pollicis longus, and a massive muscular complex located between the thumb and the thenar pad. By topology it might be inferred that this complex is formed by the m. abductor pollicis brevis, the m. flexor pollicis brevis and the m. adductor pollicis brevis. Longitudinal histological sections of the thenar pad stained with hematoxylin-eosin showed a thick layer of keratin at the distal end, external face. The observation of live specimens of C. talarum foraging on two food items of different size and filmed at 300 fps showed that the thenar pad acts as an opposable thumb, with digit-like movements. Tuco-tucos are able to perform more precise movements than expected, and to grasp and manipulate the food with one hand. In previous studies, it was suggested that the thenar pad was supported by a ‘palmar ossicle’, or ‘prepollex’ (= radial sesamoid bone). Our results suggest that this sesamoid underwent a radical change on its morphology, making the thenar pad a part of the food handling system in Ctenomys, so the thenar pad might be considered a ‘false thumb’, rather than a palmar pad. It is suggested to advance on the description and functional analysis of the thenar pad, redefining the structure, since the terms used so far to define it would not be accurate.